Geographic features and tourism development in the Czech Republic - Chistyakova, G.N.; Huszti, Zs.; Zhunusova, A.R. (KSU publ., 2017)
The article deals with tourism development in the Czech Republic, which is one of the leading and most dynamic economic sectors in many countries and is recognized as an economic phenomenon of the century. The main objective of the study is to identify a dynamic demand for tourism and the usage of its potential in the country. Applying the random method, the authors found out tourist vacation preferences, what criteria they take into account when choosing a country for leisure, what goals are pursued and how the service in that country is assessed. Comparing the tourist potential of the two countries, the authors believe that Kazakhstan with a great uniqueness of the natural and historical component, has all the necessary conditions for the tourism cluster development to meet world standards. Developing this economic sector ensures an opportunity to develop and make the country appealing to the world.
Чех Республикасының жағрафиялық ерекшеліктері мен туризмнің дамуы
Географические особенности и развитие туризма в Чешской Республике
Keywords: the Czech Republic; the Republic of Kazakhstan; tourist cluster; tourism; random research method; UNESCO; recreation; Schengen visa; entertainment industry; health resort tourism; cultural and cognitive tourism; business tourism; sports (active) tourism; religious tourism; beach tourism